2021
DOI: 10.31083/j.ejgo4205154
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life scales in women diagnosed with gynecological and breast cancer: the role of resilience. A systematic review

Abstract: Resilience and health-related quality of life are factors to be valued today in all types of patients for their relationship to wellbeing and health. Any stressful situation can significantly impact quality of life and resilience and there are numerous scales to rate these aspects. The main objective of this review is to describe the most used health-related quality of life and resilience scales in gynecological and breast cancer patients to highlight the limitations. Data sources: A review of literature in Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…As VMS is a significant symptom in women with breast cancer undergoing chemotherapy, we further explored potential factors influencing VMS and found that occupational status, chemotherapy stage, and resiliency were associated with VMS. In addition, resiliency was associated with VMS in a previous study 45 . These findings emphasize the significance of resiliency in mitigating VMS in women with breast cancer undergoing chemotherapy.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…As VMS is a significant symptom in women with breast cancer undergoing chemotherapy, we further explored potential factors influencing VMS and found that occupational status, chemotherapy stage, and resiliency were associated with VMS. In addition, resiliency was associated with VMS in a previous study 45 . These findings emphasize the significance of resiliency in mitigating VMS in women with breast cancer undergoing chemotherapy.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, resiliency was associated with VMS in a previous study. 45 These findings emphasize the significance of resiliency in mitigating VMS in women with breast cancer undergoing chemotherapy. Employed participants had relatively few menopause symptoms, which is inconsistent with the results of a previous study performed in the UK.…”
Section: Relationship Between Multiple Factors and Menopause Symptoms...mentioning
confidence: 81%
See 2 more Smart Citations